Civic participation as a precursor to political participation: a look at Malaysian youths - Samsuddin, Jamali; Lai, Che Ching; Hasan, Hamisah (Penerbit Universiti Malaysia Sabah, 2019)
The problem of political apathy has been discussed and studied across time, space and cultures with increasing importance. Evidence of youth disengagement has been well documented in all parts of the world. This led to the rise in civic activities as governments struggled with wavering democracies. In a landmark study, Putnam found a direct positive association between civic participation and democracy. However, his hypothesis could only be generalized for Italy. This study broadened Putnam’s work by testing his theory in the South East Asia, a region far different from Europe. Data were collected through a national survey (N = 5,237), sampling youths aged from 15 to 25 years old. Reaffirming Putnam’s hypothesis, the study found a strong positive relationship between civic and political participation. The discussion highlighted the role of third sector organizations to promote civic activities, which require support from both public and private sectors.